(untitled) (Economic and Political Thought, 2017)
On the basis of the entrepreneurial strategy school and leadership theory we draw the conclusion that firms managed by strong charismatic leaders exclusively responsible for the strategy formulation have higher volatility of results than firms with a planned and more predicable formal, corporate approach to strategy formulation. It is so because a strong charismatic leader may have a clear and solid vision, however he might be wrong and his vision could result in a significant failure. As a charismatic leader has a strong influence on all stakeholders his decisions are usually unquestioned and his power and his decisions affect the major dependent variable – organisational performance. Furthermore, we argue that the entrepreneurial school is usually employed in the early stages of a firm’s life cycle. As the firm matures the role of entrepreneurial visionary strategies scales down leaving the place for a more formalised planning process. However, in some cases an entrepreneurial visionary strategist is necessary even at the mature stages of the organisation life-cycle when the company is a in difficult, turbulent position as well as in a fierce competitive environment. The entrepreneurial strategic approach is the most suitable for some types of organisations where other approaches would not be so successful. Our findings indicate that a single charismatic leader’s strategic management could result in a terrific success or in a terrible failure. However, the entrepreneurial strategic approach should not be mixed with the formal planned approach of strategic management. These two perspectives at least in some type of organisations are mutually exclusive because of different fundamental assumptions. While in separation they could be successful, together they result in a failure.